2020
DOI: 10.1002/app.50215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of dialdehyde cellulose/amino‐functionalizedMCM‐41 core‐shellmicrospheres as a new eco‐friendly flame‐retardant nanocomposite

Abstract: Using proper flame‐retardant materials when constructing buildings or fabricating devices is the most important fire safety guidelines. The halogen and phosphorus‐based compounds are among the most effective flame retardants. However, most of these compounds are recognized to have a harmful effect on human body and the environment during combustion. In this context, we designed and synthesized a new eco‐friendly flame‐retardant nanocomposite by combining dialdehyde cellulose (DAC) and amino‐functionalized meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…19 Daglar et al 20 also assert that the addition of silica nanoparticles enhances the flame retardancy of the polymer and prevents dripping during the UL-94 test. Mohamed et al 21 demonstrated that silica nanocomposites synthesized from dialdehyde cellulose (DAC) and amino-functionalized mesoporous silica MCM-41 (N-M-41) could effectively increase the carbon yield, thus reducing the heat release rate, and improve the refractory properties of the polymer. Therefore, the SA could be served as the modifier to mitigate geopolymer coatings' sedimentation during filming, enhance its fire resistance, and improve its rheology in theory.…”
Section: Introductionmentioning
confidence: 99%
“…19 Daglar et al 20 also assert that the addition of silica nanoparticles enhances the flame retardancy of the polymer and prevents dripping during the UL-94 test. Mohamed et al 21 demonstrated that silica nanocomposites synthesized from dialdehyde cellulose (DAC) and amino-functionalized mesoporous silica MCM-41 (N-M-41) could effectively increase the carbon yield, thus reducing the heat release rate, and improve the refractory properties of the polymer. Therefore, the SA could be served as the modifier to mitigate geopolymer coatings' sedimentation during filming, enhance its fire resistance, and improve its rheology in theory.…”
Section: Introductionmentioning
confidence: 99%